Evaluating continuity of care incorporating a time protective effect of general practitioner care on diabetes related potentially preventable hospitalisations: An application of threshold effects model. (7th November 2019) - Ha, Ninh; Harris, Mark; Preen, David; Moorin, Rachael
No abstract available